2021
DOI: 10.3389/fonc.2021.607989
|View full text |Cite
|
Sign up to set email alerts
|

AGAP2-AS1 May Promote the Occurrence and Development of Glioblastoma by Sponging miR-9-5p: Evidence From a ceRNA Network

Abstract: Glioblastoma (GBM), the primary malignant brain tumor, is typically associated with a poor prognosis and poor quality of life, mainly due to the lack of early diagnostic biomarkers and therapeutic targets. However, gene sequencing technologies and bioinformatics analysis are currently being actively utilized to explore potential targets for the diagnosis and management of malignancy. Herein, based on a variety of bioinformatics tools for the reverse prediction of target genes associated with the prognosis of G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 47 publications
(44 reference statements)
0
3
0
Order By: Relevance
“…In our study, we identified 20 prognostic lncRNAs and revealed that these prognosis-related lncRNAs were dysregulated in glioma. It was suggested that AGAP2-AS1 overexpression was an unfavorable prognostic factor in many carcinomas, such as lung carcinoma and glioma [27][28][29]. In GBM, AGAP2-AS1 has been identified as an oncogenic gene that regulates GBM cell motility and invasion.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, we identified 20 prognostic lncRNAs and revealed that these prognosis-related lncRNAs were dysregulated in glioma. It was suggested that AGAP2-AS1 overexpression was an unfavorable prognostic factor in many carcinomas, such as lung carcinoma and glioma [27][28][29]. In GBM, AGAP2-AS1 has been identified as an oncogenic gene that regulates GBM cell motility and invasion.…”
Section: Discussionmentioning
confidence: 99%
“…MiR-100-5p downregulation in pancreatic ductal adenocarcinoma (PDAC) [ 47 ], oral squamous cell carcinoma [ 48 ], prostate cancer [ 49 , 50 ], lung cancer [ 51 ], bladder cancer [ 52 ], endometrial carcinoma [ 53 ] and breast cancer [ 54 , 55 , 56 ] contributes to tumor progression by regulating cell tumor proliferation, the response to therapy, migration, invasion or stemness. MiR-9 is also described as a negative regulator of tumor cell proliferation, invasion or drug resistance in pancreatic cancer cells [ 57 ], PDAC [ 47 ], hepatocellular carcinoma [ 58 ], gastric cancer [ 59 ], prostate cancer [ 60 ] or GBM [ 61 , 62 , 63 ]. The non-coding RNA let-7d can have different targets and effect in tumors [ 64 ].…”
Section: Discussionmentioning
confidence: 99%
“…LncRNA AGAP2 antisense RNA 1 ( AGAP2-AS1 ), transcribed from a gene located at 12q14.1, a novel cancer-related lncRNA, was dysregulated in cancers ( 42 ). In GBM, lncRNA HOTAIRM1 ( 43 , 44 ) and AGAP2-AS1 ( 45 , 46 ), as oncogenic factors, promoted tumorigenesis, predicted a poor clinical outcome, and were potential biomarkers and therapeutic targets. Keratin 8 (KRT8), a major component of the intermediate filament cytoskeleton, promotes tumor progression and metastasis of various cancers ( 47 49 ).…”
Section: Discussionmentioning
confidence: 99%